The geomorphometric atlas of Romania: an open-access database on landform classifications and morphometric variables - Andrei Ioniță; Mădălin Lungu; Marta Baleț; Andreea Todor (Journal of Maps)
This paper presents the first digital geomorphometric atlas of Romania. It primarily includes existing international classifications of landforms, as well as land-surface variables (LSVs) derived from Forest and Buildings removed Copernicus Digital Elevation Model (FABDEM) at a resolution of 30 m. Besides the standard moving window of 3 × 3 (90 × 90 m), most LSVs were also derived in moving windows of 11 × 11 (330 × 330 m), and 27 × 27 (810 × 810 m), which represent the topographic grain values specific to the Romanian topography. Up to this point, the atlas contains 10 sets of landform classification data including the geomorphons and 24 sets of LSVs as follows: Slope, Aspect, Sin (Eastness), Cos (Northness), Profile Convexity, Plan Convexity, Longitudinal Curvature, Cross-Sectional Curvature, Minimum Profile Convexity and Multidirectional Hillshade. The data are available open-source for both interactive visualizations on the ArcGIS Online platform and for download on the Google Drive platform.